A rare case of true thyroglossal fistula diagnosed by computed tomography fistulography. Issue 4 (July 2015) - Singh, Gautam Bir; Arora, Rubeena; Sherwani, Poonam; Garg, Sunil; Shukla, Shailaja; Kumar, Deepak
Abstract True thyroglossal fistula, i.e. a complete fistulous tract extending from the skin of the neck to the base of tongue is an extreme rarity with only one case reported in the medical literature. Mostly, the thyroglossal cyst ruptures and forms a discharging sinus which is erroneously labelled as a thyroglossal fistula. With this background we present one such rare case of true thyroglossal fistula in a paediatric patient, hitherto unreported in medical literature. This 13-year-old female presented to us with a discharging sinus following burst abscess. Radiological evaluation revealed a true thyroglossal fistula. Further, this clinical record also highlights the importance of computed tomography fistulography in thyroglossal tract anomalies.